(untitled) (The Peerian Journal, 2025)
This work considers the physicochemical properties of iron compounds present in natural waters, as well as factors affecting their form, behavior and stability. Particular attention is paid to the distribution of iron in divalent (Fe²⁺) and trivalent (Fe³⁺) forms, their interaction with components of the aquatic environment, as well as the processes of oxidation, reduction and precipitation. Water samples from various natural sources were analyzed to determine the total iron concentration and its individual forms, as well as the parameters affecting it - pH, Eh, temperature and degree of mineralization. The results obtained allow for a deeper understanding of iron migration in natural water bodies, as well as an assessment of the risks associated with exceeding the maximum permissible concentration. The work may be useful for specialists in the field of water supply, ecology and hydrochemistry